Examining the Utilization and Impact of Instructional Materials on Biology Education in Awka South Local Government Area - Tochukwu Ebuka Umeohana (Papanda Journal of Mathematics and Science Research, 2024)
This study aims to examine the utilization and impact of instructional materials on biology education within Awka South Local Government Area.The research employs a descriptive survey methodology to gather data from secondary school teachers and students in the area. To ensure representative sampling, 38 biology teachers were randomly selected. Data collection was facilitated through a self-structured 4-point rating questionnaire comprising sections for personal data and items related to the research questions.Descriptive statistics were utilized to analyze the extent of usage of instructional materials among teachers. The findings reveal a diverse extent of usage of instructional materials among teachers, with certain materials being employed more extensively than others. While traditional tools like audio and video recorders, projectors, and microphones are utilized to a limited extent, innovative resources such as organ tissue specimens and multimedia aids exhibit greater usage. Results indicate that access to information and communication technology (ICT) facilitates students' ability to gather recent information, while the regular use of instructional materials promotes easy comprehension of difficult concepts and enhances students' abilities and interests in biology.Recommendations include providing educators with adequate training and resources to effectively incorporate instructional materials into their teaching practices, thereby optimizing the learning experience in Awka South Local Government Area.